Upaya Meningkatkan Pemahaman Siswa Dengan Menggunakan Metode Stop Think Do (Std) - Imam Syaefulloh Hady Pratama (Al-Aulad: Journal of Islamic Primary Education, 2019)
The purpose of knowing students 'understanding in Islamic Culture History (SKI) subjects before using Stop Think Do (STD) method, applying through STD method, and increasing students' understanding after using STD method in class IV MI. The method used in this study is classroom action research (CAR).Based on the results of data analysis before using the STD method the average value obtained by students was only 56.00 with a percentage of classical achievement of 20%. After applying the STD method the results obtained in the observation of teacher activity in the first cycle 65% were quite active and in the second cycle 94.50% were very active categories. While the results obtained in the observation of student activity in the first cycle were 63.50% of the category was quite active and in the second cycle 85% were very active categories. Furthermore the reality of students' understanding after using the STD method obtained the value in the first cycle 75.00 with the percentage of classical achievement 50% enough category, and in the second cycle 89.00 with the percentage of classical achievement 90% good category.